2020
DOI: 10.3390/e22030327
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Adhesive Additives on Silica Gel Water Sorption Properties

Abstract: Adsorption chillers are characterized by low electricity consumption, lack of moving parts, and high reliability. The disadvantage of these chillers is their large weight due to low adsorbent sorption capacity. Therefore, the attention is turned to finding a sorbent with a high water sorption capacity and enhanced thermal conductivity to increase chiller efficiency. The article discusses the impact of selected adhesives used for the production of an adsorption bed in order to improve heat exchange on its surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Studies have been reported on a specific class of hygroscopic hydrogels that can collect water from ambient air thanks to their hydrophilic functional groups (-OH, -COOH, -SO 3 H, and -NH 2 ). [112] Compared to other well-known water absorbent materials such as zeolites [113] and silica gel, [114] hygroscopic hydrogels have lower activation energy for dehydration, which is a crucial property for facilitating the continuous operation of HEGs As introduced in Section 2.1, utilizing hygroscopic hydrogel and ionic polymer to generate electricity from the moisture has been reported. [36] Unlike deliquescent salts, hydrogels can maintain the integrity of their structure after absorbing and releasing quantities of water, which is beneficial for device construction and reliability during operation.…”
Section: Hygroscopic Materials For Moisture Absorptionmentioning
confidence: 99%
“…Studies have been reported on a specific class of hygroscopic hydrogels that can collect water from ambient air thanks to their hydrophilic functional groups (-OH, -COOH, -SO 3 H, and -NH 2 ). [112] Compared to other well-known water absorbent materials such as zeolites [113] and silica gel, [114] hygroscopic hydrogels have lower activation energy for dehydration, which is a crucial property for facilitating the continuous operation of HEGs As introduced in Section 2.1, utilizing hygroscopic hydrogel and ionic polymer to generate electricity from the moisture has been reported. [36] Unlike deliquescent salts, hydrogels can maintain the integrity of their structure after absorbing and releasing quantities of water, which is beneficial for device construction and reliability during operation.…”
Section: Hygroscopic Materials For Moisture Absorptionmentioning
confidence: 99%
“…Due to the low desorption temperature, low cost, and a lack of negative impact on the environment, the silica gel-water vapor working pair is commonly used in adsorption chillers [3]. Silica gel has a fairly large specific surface area (wide pores, 250-350 m 2 /g; narrow porosity, 600-850 m 2 /g), thanks to which it is possible to adsorb a large amount of water vapor [2,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The IIR also predicts that power consumption of cooling equipment may double by 2050 [3]. In 2017, the number of new air conditioning devices was 110 million units, an increase of 8.1% over 2016 [5].…”
Section: Introductionmentioning
confidence: 99%
“…Heat transfer within the bed is hampered by the high thermal resistance of the porous adsorbent [45]. Its improvement can be achieved in several ways, which mainly include increasing the heat transfer surface in the bed, increasing the heat transfer at the heat exchanger-adsorbent interface and increasing the heat transfer inside the bed by increasing the thermal conductivity of the material filling the bed [5,24,28,31]. The first method is related to increasing the surface area of the heat exchanger.…”
Section: Introductionmentioning
confidence: 99%